DNA Editing by APOBECs: A Genomic Preserver and Transformer. Issue 1 (January 2016) - Knisbacher, Binyamin A.; Gerber, Doron; Levanon, Erez Y.
Abstract : Information warfare is not limited to the cyber world because it is waged within our cells as well. The unique AID (activation-induced cytidine deaminase)/APOBEC (apolipoprotein B mRNA editing enzyme, catalytic polypeptide) family comprises proteins that alter DNA sequences by converting deoxycytidines to deoxyuridines through deamination. This C-to-U DNA editing enables them to inhibit parasitic viruses and retrotransposons by disrupting their genomic content. In addition to attacking genomic invaders, APOBECs can target their host genome, which can be beneficial by initiating processes that create antibody diversity needed for the immune system or by accelerating the rate of evolution. AID can also alter gene regulation by removing epigenetic modifications from genomic DNA. However, when uncontrolled, these powerful agents of change can threaten genome stability and eventually lead to cancer. Trends: APOBECs, a family of C-to-U DNA deaminases, are an enzymatic source of mutations. DNA editing by AID/APOBECs serves in diverse biological functions. APOBECs defend the genome from viruses and retrotransposons. Genomic DNA editing by APOBEC3A and APOBEC3B increases mutation loads in cancer. DNA editing of retrotransposons accelerates evolution by increasing genomic sequence diversity.